Key Success Factors and Future Perspective of Silicon-Based Solar Cells. (5th March 2013) - Binetti, S.; Acciarri, M.; Le Donne, A.; Morgano, M.; Jestin, Y.
Abstract : Today, after more than 70 years of continued progress on silicon technology, about 85% of cumulative installed photovolatic (PV) modules are based on crystalline silicon (c-Si). PV devices based on silicon are the most common solar cells currently being produced, and it is mainly due to silicon technology that the PV has grown by 40% per year over the last decade. An additional step in the silicon solar cell development is ongoing, and it is related to a further efficiency improvement through defect control, device optimization, surface modification, and nanotechnology approaches. This paper attempts to briefly review the most important advances and current technologies used to produce crystalline silicon solar devices and in the meantime the most challenging and promising strategies acting to increase the efficiency to cost/ratio of silicon solar cells. Eventually, the impact and the potentiality of using a nanotechnology approach in a silicon-based solar cell are also described.